A STUDY OF CONSUMER CREDIT BEHAVIOR IN SRI LANKA GOLD MARKET - Malwatta, Y.; Amaratunge, S.; Withanawasam, M.P.K. (International Conference of Japanese Graduates’ Alumni Association in Sri Lanka, 2016)
Attached